Bending strength capacity of RC interlocking joint panels / Megat Iqbal Faris Zainuddin - Zainuddin, Megat Iqbal Faris (Faculty of Civil Engineering, 2013)
Precast concrete panels are used extensively in high rise construction due to its advantage in saving time and work with great quality. The connections between interlocking panels are vitally crucial since they affect both performance and homogenous of structure. The depletion of natural aggregate sources and increase amount of waste concrete from construction promote the application of crushed concrete waste aggregate (CCwA) in structure. This study was conducted to determine the bending strength capacity and mode of failure in reinforced concrete interlocking joint panels by using crushed concrete waste aggregate (CCwA). Two (2) set of interlocking panels with dimension of 75 mm x 900 mm x 500 mm (thickness, length and height) were subjected to three point load at the connection located in the midspan of panels. In comparison, the results shows that the interlocking joint panels with CCwA are passing the entire requirement in specified MS and BS. This is showing that interlocking panels with CCwA can be an alternative in replacing the natural aggregates. The study shows that the interlocking panels using CCwA under three loading points are good enough to be used in industry. This will promote application of interlocking panel in construction and give out a solution on the wastage of construction material and shortage in natural aggregate.